2014 IEEE International Conference on Robotics and Automation (ICRA) 2014
DOI: 10.1109/icra.2014.6906619
|View full text |Cite
|
Sign up to set email alerts
|

MIRA: Enabler of mass customization through agent-based development of intelligent manufacturing systems

Abstract: This research proposes an innovative agent-based design method known as "MIRA" (Modular, Intelligent and Real-time Agent) to represent products as well as mechatronic components in manufacturing systems. The new agent exploits semantic knowledge representation of its capabilities, tasks and surroundings, and upon which performs rule-based reasoning leading to generation of the IEC 61499 Function Blocks for real time and distributed control of production systems. This approach facilitates product's mass customi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…The higher frequency of studies could be observed in the fast food category (12), wich can be verified several food products, such as MC application for pizza production (WEGRZYN et al, 2012;LIPTON et al, 2015;NAGPAL;LEI;KHARE, 2015;SUN et al, 2015), hot dogs (RAHIMNIA; MOGHADASIAN; CASTKA, 2009; PULLMAN; VERMA; GOODALE, 2001), hamburger (PULLMAN; VERMA; GOODALE, 2001; WOLF; ZHANG, 2016), salads (NAGPAL; LEI; KHARE, 2015) and ready restaurants dishes (SAMSUDIN et al, 2011;CHEN et al, 2014). The MC applications also can be verified in: beverages category, such as juices (FERREIRA; ALCÂNTARA, 2015), beers (DONADINI et al, 2016) and wines (Van Hoeck); Condiments category, such as tomatoes products (FERREIRA, ALCÂNTARA, 2016) and olive oil (BALCOMBE et al, 2016); candies category, such as cakes, chocolates, cokies (WEGRZYN et al, 2012;LIPTON et al, 2015;SUN et al, 2015) and ice cream (SOROURI et al, 2014); and dairy foods category with a higher frequency of studies about MC applications in yoghurts (FISHER et al, 2005;MCINTOSH et al, 2010; MATTHEWS; MCINTOSH; MULLINEUX, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher frequency of studies could be observed in the fast food category (12), wich can be verified several food products, such as MC application for pizza production (WEGRZYN et al, 2012;LIPTON et al, 2015;NAGPAL;LEI;KHARE, 2015;SUN et al, 2015), hot dogs (RAHIMNIA; MOGHADASIAN; CASTKA, 2009; PULLMAN; VERMA; GOODALE, 2001), hamburger (PULLMAN; VERMA; GOODALE, 2001; WOLF; ZHANG, 2016), salads (NAGPAL; LEI; KHARE, 2015) and ready restaurants dishes (SAMSUDIN et al, 2011;CHEN et al, 2014). The MC applications also can be verified in: beverages category, such as juices (FERREIRA; ALCÂNTARA, 2015), beers (DONADINI et al, 2016) and wines (Van Hoeck); Condiments category, such as tomatoes products (FERREIRA, ALCÂNTARA, 2016) and olive oil (BALCOMBE et al, 2016); candies category, such as cakes, chocolates, cokies (WEGRZYN et al, 2012;LIPTON et al, 2015;SUN et al, 2015) and ice cream (SOROURI et al, 2014); and dairy foods category with a higher frequency of studies about MC applications in yoghurts (FISHER et al, 2005;MCINTOSH et al, 2010; MATTHEWS; MCINTOSH; MULLINEUX, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The development of software for process simulation could predict the changes in the quality of food products subjected to operations. Nevertheless, the availability of systems with this feature is still limited in food industry, 2001x Coulston et al (2003) x German et al (2004) x x Grunert (2005) x x x Fisher et al (2005) x x x x x Nowak- Wegrzyn (2007) x Sun (2007) x x x x x Boland (2008) x x x x Kumar (2008) x Awazu et al (2009) x x Dorman et al (2009) x x Rahimnia, Moghadasian and Castka (2009) x x Gehlhar et al (2009) x x Mahalik and Nambiar (2010) x 2014x Sorouri et al (2014) x Poínhos et al (2014) x Chen et al (2014) x x Haugaard, Brockhoff and Lähteenmäki (2016) x Keenan et al (2015) x x Lipton et al (2015) x x Nagpal, Lei and Khare (2015) x x x x Sun et al (2015) x x Ferreira and Alcântara (2015) x x x x Adeigbe et al (2015) x x Ferreira and Alcântara (2016) x x x x Balcombe et al (2016) x x Donadini et al (2016) x x x Hankammer et al (2016) x Wolf and Zhang (2016) x very reason that software developers have added strength to invest resources in the development of specific food processing capabilities (HALDER et al, 2011). A feature of the software, in general, is that components in a virtual environment can be multiplied easily and at low cost (VERDOW; BEULENS; WOLFERT, 2014), which enables customization.…”
Section: Foods Processing and Its Enablersmentioning
confidence: 99%
“…Ainda para a categoria de doces, Sorouri et al (2014) sugeriram a utilização de um sistema mecânico automatizado e inteligente para a fabricação de sorvetes. Para a categoria dos alimentos "lácteos", foi identificada maior frequência de estudos com aplicações da CM em iogurtes (FISHER et al, 2005;McINTOSH et al, 2010;MATTHEWS et al, 2011).…”
Section: Calegari L P; Fettermann D Cunclassified
“…This design approach is applicable to a wide range of production systems, regardless of their size: from a small automated shop which receives its orders directly from customers, to large manufacturing systems, where all the information, regarding production rules and equipment, is provided from the enterprise level. The MIRA approach for control software design of customized production system has been described in [12,13] ,and in this paper the collaboration aspect of MIRAs is elaborated. Figure 1.…”
Section: Mira Design Approachmentioning
confidence: 99%
“…The way MIRAs' knowledge is shaped for manufacturing is similar to IMCs and is based on the STEP method [12] as illustrated in Figure 2. Sc is provided to a C-MIRA by product designers who define a detailed specification of the production by an orderly set of operations (or recipe) that a product has to undergo to be produced [2].…”
Section: Knowledge Representation Of Mirasmentioning
confidence: 99%